The Old Testament Pseudepigrapha ; v. 2 - Charlesworth, James H. (New York, NY Doubleday, 1983)
Contents : v. 2 : Expansions of the "Old Testaments" and Legends, Wisdom and Philosophical Literature, Prayers, Psalms and Odes, Fragments of lost Judeo-Hellenistic Works. Includes bibliographical references and index.
Keywords: Apocryphal books (Old Testament) -- criticism, interpretation, etc